The influence of tectonic disturbances on the gas content of coal-bearing deposits of the Lyubelya field of the Lviv-Volyn coal basin - Matrofailo, M.M. (Geofizicheskiy Zhurnal, 2025)
The paper describes the gas content of the coal seams of the Lyubelya deposit of the Lviv-Volyn coal basin. According to methane, carbon dioxide, and nitrogen content, methane-nitrogen and methane zones are distinguished in the field. Structural and tectonic features of the Carbonaceous deposits were characterized based on geological exploration and thematic studies. The influence of geodynamic processes of formation of the territory of the Lviv-Volyn basin on the degassing of coal deposits is indicated. The main factors affecting the accumulation of hydrocarbon gases in the coal-bearing stratum of the Lyubelyacoal field were determined.